A qualitative correlation between engine exhaust particulate number and mass emissions. (15th August 2017) - Shukla, Pravesh Chandra; Gupta, Tarun; Gupta, Neeraj; Agarwal, Avinash Kumar
Highlights: A unique method developed to correlate particle number and mass emissions. Established relationship is found to depend on engine operating condition. Particle mass is dominant over particle number emissions at lower loads. At intermediate loads, both particle number and mass emissions reduced significantly. DOCs showed significant reduction in particle number and mass emissions. Abstract: Diesel particulate are designated as 'carcinogenic'. In this study, a novel approach has been adopted to determine the relationship between particle mass and particle number emissions from a four-cylinder naturally aspired water-cooled transport diesel engine, which is fuelled by mineral diesel and 20% (v/v) Karanja biodiesel blend (B20) under different engine operating conditions. This approach involves establishing a relationship between particle number-mass emissions by mapping the inclination of identified particulate size concentrations for their dominating contribution towards either particle number or particulate mass. Established relationship is found to be dependent on engine operating condition. Experiment were performed on (i) raw engine exhaust, (ii) exhaust from a commercial diesel oxidation catalyst (DOC1 ) and (iii) exhaust from two in-house prepared DOCs (named as DOC2 and DOC3 ). Prepared DOCs were coated with Co-Ce mixed oxide and lanthanum perovskite based catalysts. Results obtained by applying this approach exhibited nearly similar particulate emission characteristics for test fuels, mineral diesel and B20. This technique can therefore be successfully adopted for particulate characterization.